Illustrated Dictionary and Resource Directory of Environmental and Occupational Health - Koren, Herman (CRC Press, 2004)
A globally recognized resource for the vast and diverse collection of interrelated terms and topics, this volume encompasses the fields of environmental science, occupational health and safety, and preventive medicine. The second edition of a bestseller, it contains 16,000 terms that reflect the steady evolution of this multi-disciplinary field, including over 8500 new terms related to epidemiology, equipment and environmental control, new and emerging diseases, hazardous chemicals, bioterrorism and emergency response, and environmental resources. It contains more than 1,000 detailed illustrations that help you visualize the concepts and lists hundreds of resources.